2022
DOI: 10.3390/diagnostics12061396
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Analysis of Patients with COVID-19 in Mexico Based on Risk Factors Applying Machine Learning Techniques

Abstract: The new pandemic caused by the COVID-19 virus has generated an overload in the quality of medical care in clinical centers around the world. Causes that originate this fact include lack of medical personnel, infrastructure, medicines, among others. The rapid and exponential increase in the number of patients infected by COVID-19 has required an efficient and speedy prediction of possible infections and their consequences with the purpose of reducing the health care quality overload. Therefore, intelligent mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 84 publications
0
5
1
Order By: Relevance
“…12 These comorbidities present a low grade chronic inflammation producing adipokines and cytokines promoting an adequate scenario for susceptibility to infection such as SARS-CoV-2, and therefore this virus could enhance the pre-existing inflammation resulting in a more severe COVID-19 outcome. 13 The mortality risk has been reported as increased in patients COVID-19 with intubation requirement, 14 in Mexico, having an age ≥ 60 years and hypertension had been reported like factors risk to death, however, in our study, we found that overweight and T2D were the main mortality risk factors risk, this reflect the public health problem of high prevalence of non-communicable diseases we suffer in Mexico, and the imperious necessity for their control.…”
Section: Wwwmedigraphicorgmxcontrasting
confidence: 62%
“…12 These comorbidities present a low grade chronic inflammation producing adipokines and cytokines promoting an adequate scenario for susceptibility to infection such as SARS-CoV-2, and therefore this virus could enhance the pre-existing inflammation resulting in a more severe COVID-19 outcome. 13 The mortality risk has been reported as increased in patients COVID-19 with intubation requirement, 14 in Mexico, having an age ≥ 60 years and hypertension had been reported like factors risk to death, however, in our study, we found that overweight and T2D were the main mortality risk factors risk, this reflect the public health problem of high prevalence of non-communicable diseases we suffer in Mexico, and the imperious necessity for their control.…”
Section: Wwwmedigraphicorgmxcontrasting
confidence: 62%
“…Several studies have demonstrated that the clinical severity and disease burden of COVID-19 are associated with age structure, vaccination status, underlying disease status, accessibility of medical resources, and other factors [13][14][15]. Possible explanatory variables and their definitions are shown in S7 Table . We first explored possible factors by calculating Spearman correlation coefficients.…”
Section: Association Analysismentioning
confidence: 99%
“…Subsequently, we conducted random forest regression to explore the inf luence of multiple factors simultaneously [13]. Furthermore, we used the eXtreme Gradient Boosting (XGBoost) [16] model to explore the overall correlations for whole samples and the specific correlation between factors and indicators in Shanghai and Hong Kong, China.…”
Section: Association Analysismentioning
confidence: 99%
“…Finally, Figure 2 shows the percentages of use of the metrics in the articles reviewed in this work. Regarding the performance of the algorithms used in the prediction models, many studies evaluate and compare two or more metrics (we found in the study papers that they evaluated at least five algorithms [59,60,67,76,77,86]), and to facilitate the understanding of the results, this analysis selected the metrics that reported the best performance within each study. Consequently, Table 6 contains the average of the best values presented by the metric in each study.…”
Section: Algorithmsmentioning
confidence: 99%